1997
DOI: 10.2307/2265895
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Aquatic Primary Productivity: Experiments Under Nutrient- and Light-Limited Conditions

Abstract: To explore the interactive effect of physical dimension and nutrient conditions on primary productivity, experimental planktonic-benthic ecosystems were initiated in different-sized cylindrical containers scaled in two ways. One series of experimental ecosystems was scaled for a constant depth (1.0 m) as volume was increased from 0.1 to 1.0 to 10 m 3 . The other series was scaled for a constant shape (radius/depth ϭ 0.56) across an identical range of volumes. Triplicate systems of each size and shape were hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…Although the method has several advantages and avoids the caveats of bottle and chamber incubations (Gerhart and Likens 1975;Bender et al 1987;Petersen et al 1997Petersen et al , 1999Chen et al 2000), a number of uncertainties and assumptions are, however, also associated with the current application of the technique that need consideration (Table 7). Regardless of these issues, buoy-based data are being collected from an increasing number of lakes around the world, making it possible to investigate changes in metabolism over large gradients in time and space.…”
Section: Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the method has several advantages and avoids the caveats of bottle and chamber incubations (Gerhart and Likens 1975;Bender et al 1987;Petersen et al 1997Petersen et al , 1999Chen et al 2000), a number of uncertainties and assumptions are, however, also associated with the current application of the technique that need consideration (Table 7). Regardless of these issues, buoy-based data are being collected from an increasing number of lakes around the world, making it possible to investigate changes in metabolism over large gradients in time and space.…”
Section: Future Researchmentioning
confidence: 99%
“…In the past, metabolism has been measured in bottles and chambers incubated at varying irradiance levels, using either dissolved oxygen or carbon (as 14 C) as an elemental tracer. By extrapolating bottle rates to represent 24-h periods, it is possible to calculate depth-and time-integrated pelagic rates of GPP, NEP, and R; and when combined with sediment chamber incubations, it is possible to estimate GPP, NEP, and R of entire ecosystems (e.g., Kemp et al 1997;Gazeau et al 2005). While enclosing part of an aquatic system within bottles is attractive because it allows precise measurements with replication, incubations are significantly affected by "container effects," which hamper estimates of ecosystem level metabolism (Bender et al 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Free-water methods have considerable advantages over incubation approaches in either light and dark bottles or benthic chambers. Container effects including enclosure in bottles, sediment chambers, and various other devices can be significant, and comparison among container studies is difficult because many studies fail to report key details of the containers used (Petersen et al 1997;Petersen et al 1999). Additionally, container approaches suffer from problems of scale (Gerhart and Likens 1975;Chen et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Mazumder (1994) demonstrated that the phosphorus-chlorophyll relationship is influenced by thermal mixing regime (with or without stratification) and foodweb structure (presence or absence of large-bodied Daphnid). Lake depth is suspected to have a great influence on the plankton communities and ecosystem functions through light limitation (Petersen et al 1997 …”
Section: Introductionmentioning
confidence: 99%